FTIR spectroscopic and thermogravimetric characterization of ground tyre rubber devulcanized by microwave treatment. (July 2016) - Colom, X.; Faliq, Anwar; Formela, K.; Cañavate, J.
Abstract: In this work, the phenomena involved in the microwave devulcanization of ground tyre rubber (GTR) were investigated. Three types of GTR with different content of organic compounds (elastomers, plasticizers, etc.), carbon black and ash have been studied. The chemical structure of GTR before and after a microwave devulcanization process was analyzed by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). Furthermore, the efficiency of the microwave devulcanization conducted at different treatment time was evaluated based on the values of crosslinking density and sol fraction content. FTIR spectroscopy results showed that devulcanization of GTR causes a decrease in carbon black with generation of CO2 due to its thermo oxidation, a decrease in the structural groups related to elastomeric components (mainly methylene and methine) and a breaking of CS groups and SS bridges. The presented results indicate the strong correlation between the content of SiO2 in the GTR and the achieved degree of devulcanization. It was observed that GTRs with a high content of SiO2 are devulcanized more easily than the samples with low content of SiO2, which suggest that the presence of silica fillers improve microwave devulcanization efficiency.